موازنة بين المستصفى للغزالي وروضة الناظر لابن قدامة في المنهج والاختيار - Mustori Mustori (Al-Zahra : Journal for Islamic and Arabic Studies, 2022)
This research aims to describe and compare the methods of Imam Ghazali in writing his book al-Mustashfa and the methods of Imam Ibn Quddamah al-Maqdisi in writing his book Rawdah al-Nazir. In addition, this study aims to compare their thought, in expressing the opinions of scholars proposing jurisprudent in disputed issues. This research uses inductive and analytical methods by analyzing the opinions of Imam Ghazali in his book al-Mustashfa and comparing it with the thoughts of Ibn Quddamah's jurisprudent in his al-Rawdah, as well as comparisons of the methods of drafting the book. This research belongs to the research of literature, so that researchers did not use interview techniques, but relied on sources of literature including books of jurisprudent proposals, dictionaries, and hadith books. Among the main findings in the study are that Raudhah al-Nazir's book had a close relationship with the book of al-Mustashfa and that Ibn Quddamah was deeply affected by it.